Is it time to abolish company car benefits? An analysis of transport behaviour in Germany and implications for climate change. (28th May 2019) - Metzler, Daniel; Humpe, Andreas; Gössling, Stefan
ABSTRACT: Company cars have received considerable attention because of their partial tax-exemption and the changes in travel behaviour they stimulate, including car model choices, distances driven, and car ownership patterns. This paper is the first to present evidence on actual transport behaviour change, based on mobility and fuel diaries, and comparing a sample of 624 company cars and 9328 private cars in Germany. Analysis confirms that company cars belong to the more heavily motorized car segments (with an average 97 kW, as opposed to 79 kW of private cars), and are driven more than private cars (24, 672 km per year, compared to 12, 828 km per year for private cars). Company car benefits also increase average household vehicle numbers by 25%. Results show that it is imperative to distinguish company cars of company owners relative to those driven by employees, as negative externalities increase significantly where company cars are used by the latter. Abolishing company car benefits could significantly reduce emissions from passenger road transport and stimulate change in the country's automotive industries towards a lower-carbon path. As Germany is not currently on track to meet its climate mitigation targets, this would be a timely policy shift. Key policy insights Company car benefits increase transport demand, car ownership, and average vehicle fleet engine power. These effects are particularly relevant for employees. Company cars have, in spite of their larger size and greater engine power, a (modestly) better fuel economy than private cars, possibly because they represent more recent and hence more efficient car models. A policy focus on vehicle fuel efficiency improvements will fail to reduce the German car fleet's CO2 emissions to a sustainable level. Abolishing company car benefits could yield a significant reduction in GHG emissions from passenger road transport. Company car subsidies are an out-dated mode of support for the fossil-fuel based automotive industry.